2014
DOI: 10.1007/s00404-014-3438-7
|View full text |Cite
|
Sign up to set email alerts
|

Is guideline-adherent adjuvant treatment an equal alternative for patients aged >65 who cannot participate in adjuvant clinical breast cancer trials? A retrospective multi-center cohort study of 4,142 patients

Abstract: Guideline-adherent adjuvant treatment seems to be an equivalent option for elderly breast cancer patients. There is a strong association between guideline adherence and improved outcome parameters in elderly breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Our finding that DFS was significantly longer in the younger postmenopausal patients (Group B) indirectly suggests that the older patients were potentially undertreated. A multicenter cohort study by Van Ewijk et al (2015) showed guideline-adherent treatment to be associated with an improved prognosis. In a prospective randomized study, Muss and colleagues (Muss et al 2009) compared capecitabine with standard polychemotherapy in older patients with early stage BC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that DFS was significantly longer in the younger postmenopausal patients (Group B) indirectly suggests that the older patients were potentially undertreated. A multicenter cohort study by Van Ewijk et al (2015) showed guideline-adherent treatment to be associated with an improved prognosis. In a prospective randomized study, Muss and colleagues (Muss et al 2009) compared capecitabine with standard polychemotherapy in older patients with early stage BC.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, numerous new drugs and combinations of drugs have become clinically established based on large prospective multicenter studies. However, the high proportion of older BC patients has been underrepresented in clinical studies (Lewis et al 2003;Van Ewijk et al 2015). As a result of a lack of evidence regarding optimal treatment, this patient group often does not receive guideline-based treatment (Schonberg et al 2010;Yardley 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Their characteristics and main results are available in Additional files 4 and 5. A direct association between adherence to breast cancer CGs and better overall survival was more frequently observed regardless of the study period [22], the use of different cut-offs or number of deviations to CGs recommendations used to determine adherence [17,42,48] and patient's age [17,18,37,41,44,45]. Although non-adherence was associated with lower survival rate both in triple negative breast cancer (TNBC) and non-TNBC patients, this association was stronger in TNBC than in non-TBNC patients [19,43].…”
Section: Impact On Patient Outcomes Overall Survivalmentioning
confidence: 99%
“…Additionally, this outcome was reported in another 15 studies not meeting the criteria for performing a metaanalysis as specified in the methods section. An association between adherence to breast cancer CGs and better disease-free survival was observed consistently regardless of the study period [22,47], use of different [18,19,38,45] High 0 (0%) - ‡ Percentages exceed 100% because the categories are not mutually exclusive (i.e. some studies involved more than one type of guideline and more than one type of outcome) cut-offs to determine adherence [43,47,48], patient's age [18,41] and subtype of tumour [42,43].…”
Section: Disease-free Survivalmentioning
confidence: 99%
“…We finally included 57 references representing 41 primary studies. Three studies were reported in more than one publication: BRENDA I [12,13,[20][21][22][23][24][25][26][27][28], BRENDA II [29][30][31], and OncoDoc2 [32][33][34]. (Fig.…”
Section: Study Selectionmentioning
confidence: 99%